Born in Translation and Iteration: On the Poetics of João Delgado - Lea Mauas; Diego Rotman (Arts, 2023)
João Delgado’s poetry first appeared as an anthology of translated poetry in He’arat Shulaym Issue 1, published in November 2001 in Jerusalem by the artist collective Sala-Manca. The entire issue was devoted to João Delgado. Delgado was a Portuguese-Argentinean poet, born in Lisbon circa 1920 (or not), who left Portugal as a political refugee for Buenos Aires. He disappeared in 1976 during the military dictatorship in Argentina (1976–1983). Since 1976, there has been no trace of his fate, although new fragments of his work are constantly being discovered, translated, and published by the Sala-Manca group. There is no evidence of any originals of his work. Literary critics in Israel praised Delgado’s poetry and art and even identified previously unknown relationships to poets and artists from the European avantgarde. In Sala-Manca’s artistic work, dating back two decades, João Delgado and his heteronyms would have a central role and focus, blurring the boundaries of the group, blurring the fictional with the “real”, and proposing a subjectivity that embraces multiplicity and dispersion. Translating his poetry into Hebrew, a foreign language (to Delgado), and bringing it into print for the first time in neither its original language nor the cultural context in which it was created may be seen as a kind of de-contextualization of the poet’s poetry, since Delgado always kept himself and his oeuvre connected to the immediate surroundings where it was produced. On the other hand, perhaps it is actually this possibility—to “become only in translation”—that is one of the outstanding characteristics of Delgado’s poetry, emblematic of its linguistic and conceptual elasticity. This paper examines João Delgado’s poetic work in relation to Sala-Manca’s artistic work and the way in which both Sala-Manca and Delgado create a “system of life” by being heteronyms of one another, allowing for a multiplicity of identities, and stressing the relation to Others.